2022
DOI: 10.26822/iejee.2022.265
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Collaborative Learning Techniques on Written Expression, Self- Regulation and Writing Motivation

Abstract: The study examines the effects of collaborative learning techniques on written expression, self-regulation and writing motivation. It was designed according to the pre-test-post-test control group experimental model. The research was conducted during the 2017-2018 academic year with a total of 88 students in in one control and two experimental groups. The first experimental group performed writing exercises according to Co-Op Co-Op and the second experimental group utilized the STAD technique. The control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This is caused by the factor of writing, which is the most complex skill in language, so it has the highest difficulty level. In the last ten years, several studies on writing have shown that writing strategies are essential in efforts to improve writing skills [4], [5], writing strategies [6], [7], [8], [9], [ 10], and writing motivation [11], [12], [13] which will influence other skill contexts, for example, reading or cognitive abilities. Writing is not easy because it requires complex skills and tenacity from the writer [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is caused by the factor of writing, which is the most complex skill in language, so it has the highest difficulty level. In the last ten years, several studies on writing have shown that writing strategies are essential in efforts to improve writing skills [4], [5], writing strategies [6], [7], [8], [9], [ 10], and writing motivation [11], [12], [13] which will influence other skill contexts, for example, reading or cognitive abilities. Writing is not easy because it requires complex skills and tenacity from the writer [14].…”
Section: Introductionmentioning
confidence: 99%